Magnetic resonance imaging for spinocerebellar ataxia: a bibliometric analysis based on web of science - Liu, Zhen-Yi; Zhang, Lin; Wang, Zhao-Di; Huang, Zi-Qiang; Li, Meng-Cheng; Lu, Yan; Hu, Jian-Ping; Chen, Qun-Lin; Chen, Xin-Yuan (Frontiers in Neurology, 2025)
The objective of this study was to review the history of magnetic resonance imaging (MRI) research on spinocerebellar ataxia (SCA) over the last 16 years. We conducted a comprehensive bibliometric analysis of relevant scientific literature that explores the use of MRI in studying SCA using CiteSpace. A total of 761 scientific manuscripts, published between January 2009 and March 2025 and available in the Web of Science (WoS) database, were included in this analysis. A total of 197 out of 761 articles were analyzed using CiteSpace to determine the number and centrality of publications, countries, institutions, journals, authors, cited references, and keywords related to MRI and SCA. Overall, the number of publications that use MRI to study SCA has gradually increased over the years. The United States, China, Italy, Germany, and Brazil are at the forefront in this research field; a total of 420 authors from 317 research institutions in these nations have published articles in neuroscience-related journals. Among the most cited publications are an article by Rezende et al. on brain structural damage in SCA3 patients and an review by Klockgether et al. on spinocerebellar ataxia. The keyword “spinocerebellar ataxia” has the highest frequency of occurrence. However, “feature” may become a research hotspot in the coming years based on the analysis of the keyword’s citation burst. The findings of this bibliometric study provide a summary of the last 16 years of SCA research using MRI technology. More importantly, the present study identifies current trends and future research hotspots in the field, helping researchers to identify new and unexplored research areas.